2017
DOI: 10.18632/oncotarget.18135
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the c-reactive protein/prognostic nutritional index ratio after hip fracture surgery in the elderly population

Abstract: BackgroundMore and more older patients receive the surgery after hip fracture. However, the mortality rate is high. Prognostic nutritional index (PNI) is associated with prognosis in hip fracture patients. In the current study, we proposed a novel prognostic score, named c-reactive protein/PNI ratio (CRP/PNI ratio), for predicting the prognosis for geriatric orthopedic population.MethodsThis is a prospective study. Eighty cases of hip fracture surgery in the elderly population were studied to reveal the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…A study conducted by Norring-Agerskov et al [ 8 ] found that the 30-day mortality after hip fracture was significantly associated with elevated levels of inflammation markers, such as C-reactive protein (CRP), soluble urokinase plasminogen activating receptor (suPAR), and ferritin. In addition, a series of studies have reported that many inflammation-based markers were directly related to poor prognosis or post-operative complications in patients with hip fracture, including prognostic nutritional index ratio (PNI) [ 9 ], CRP/PNI ratio [ 10 ], and neutrophil-to-lymphocyte ratio (NLR) [ 11 , 12 ]. Platelet-to-lymphocyte ratio (PLR), a novel marker of systemic inflammation, has been reported to be closely related to the prognosis of many diseases, such as inflammatory diseases [ 13 ], cardiovascular disease [ 14 ], and various malignancies [ 15 17 ], even in the 2019-novel coronavirus disease (COVID-19) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Norring-Agerskov et al [ 8 ] found that the 30-day mortality after hip fracture was significantly associated with elevated levels of inflammation markers, such as C-reactive protein (CRP), soluble urokinase plasminogen activating receptor (suPAR), and ferritin. In addition, a series of studies have reported that many inflammation-based markers were directly related to poor prognosis or post-operative complications in patients with hip fracture, including prognostic nutritional index ratio (PNI) [ 9 ], CRP/PNI ratio [ 10 ], and neutrophil-to-lymphocyte ratio (NLR) [ 11 , 12 ]. Platelet-to-lymphocyte ratio (PLR), a novel marker of systemic inflammation, has been reported to be closely related to the prognosis of many diseases, such as inflammatory diseases [ 13 ], cardiovascular disease [ 14 ], and various malignancies [ 15 17 ], even in the 2019-novel coronavirus disease (COVID-19) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic nutrition index (PNI) is used to evaluate the outcomes of patients with malignant tumors, such as esophageal cancer [8], lung cancer [9], and gastric cancer [10]. In recent work, CRP/PNI showed a prognostic ability in esophageal cancer patients [8] and fracture surgery patients [11]. Raised CRP/PNI predicted poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…(2-3 days), 3 (4-7 days), 4 (8-21 days), or 5 (> 22 days)); (ii) surgery and anaesthesia records, including the American Society of Anesthesiologists (ASA) grade, surgeons (eight chief surgeons with at least 20 years of surgical experience (surgeons A, B, C, D, E, F, G, and H) participated in this study), surgery type, anaesthesia methods, postoperative analgesic methods, duration of anaesthesia and surgery, ratio of perioperative blood transfusion, intraoperative blood loss, and intraoperative crystal and colloidal liquid infusion volumes; and (iii) laboratory results at admission, 1 day postoperatively, and before discharge ("before discharge" was de ned as the results of the latest blood test, usually within 48 h before discharge), including ALB, prealbumin (PAb), globulin (GLB), and Hb concentrations, lymphocyte (LYM) and neutrophil (NEUT) counts, neutrophil to lymphocyte ratio (NLR), and PNI. PNI was calculated using the following formula: 10 × ALB (g/dl) + 0.005 × LYM count (per mm 3 ) [13][14][15] (Table 1). AUC and optimal cut-off values of the independent factors and ALB…”
Section: Variablesmentioning
confidence: 99%
“…The prognostic nutritional index (PNI), initially proposed by Buzby et al, 12 is a comprehensive index for evaluating the nutritional status of patients undergoing surgery. 13,14 Currently, a low PNI, as a proxy for subpar perioperative nutritional status, is reportedly a signi cant predictor of poor postoperative outcomes and increased mortality in various malignancies. 15,16 However, studies on PNI focusing on the perioperative adverse outcomes of patients undergoing surgery for femoral fractures are almost nonexistent.…”
mentioning
confidence: 99%